PENGARUH PERANAN ORANG TUA DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 1 KOTA JAMBI - Redi Indra Yudha, Haryono, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to know the description of the role of parents, learning habits and student learning outcomes, and know the influence both partially and simultaneously between the role of parents and learning habits of student learning outcomes on the subjects of economy class X in SMA Negeri 1 Kota Jambi. The result of the research shows that (1) the role of parents and the habit of learning is in the less good category, (2) There is significant influence between the role of parents to student learning outcomes, (3) There is a significant influence between learning habits toward student learning outcomes, and (4) There is a significant influence between the role of parents and learning habits simultaneously on the learning outcomes of X class students economic subjects in SMA Negeri 1 Kota Jambi. Thus, the involvement of parents through the role given every day (learning children at home) will make children feel cared for and lead to positive habits (learning). Thus, it can be explained that the role of parents and learning habits indirectly will improve the acquisition of learning outcomes better than ever.Kata Kunci : Role of Parents, Habit of Learning, Learning Outcomes.